Effectiveness of Investments on the Cryptocurrency Market and Investments on the Stock Market – a Comparative Approach - Wyderka, Dominika; Saganowski, Tomasz (Journal of Finance and Financial Law, 2018)
In the online world, virtual currency systems are used more and more often. Bitcoin is the most popular and decentralized ones. The aim of the article is to assess the profitability of investments on two different markets – the stock market and the cryptocurrency market. The work also attempts to characterize bitcoin cryptocurrencies.